Retracted: Crystal Structure, Hirshfeld Surface Analysis, and HOMO-LUMO Study of 4-Ethyl-5-(2-hydroxyphenyl)-2H-1,2,4-Triazole-3(4H)-Thione - Zeba Alam; Md. Serajul Haque Faizi; Asif Jamal; Necmi Dege (Progress in Chemical Science Research Vol. 6, 2023)
An intramolecular hydrogen bonding (C H S) is found in the title compound (C10H11N3OS), which results in a thione tautomer in the solid state. The dihedral angle between the triazole and the benzene ring is found to be 85.33 (6)°. The C-H...\(π\) interactions and intermolecular hydrogen bonding such as N-H...S and O-H...N. stabilize the crystal. The hirshfeld surface analysis reveals that the H-H and S-H interactions are the main contributors to the crystal packing of the title compound. The orbital energy gap between LUMO and HOMO was found to be 4.1589 eV. This book chapter has been retracted.